The curriculum experiment : meeting the challenge of social change - Elliott, John. (Buckingham [England] : Open University Press, 1998)
"This book focuses on the interface between curriculum policy/practice and social change in technology-driven advanced societies, and the challenges this presents for education in the 21st century." "Drawing on the experience of attempts at radical innovation in the curriculum within the UK and other OECD countries, the author develops a framework for curriculum policy making and development which he argues will enable education to meet the challenges of social change. In the process, he undertakes a critique of the currently fashionable school effectiveness and improvement movements and argues that they are underpinned by outmoded views of the roles and functions of schools."--Jacket.
Includes bibliographical references and index.
Keywords: Curriculum planning -- Social aspects -- England; Curriculum change -- England; Teacher participation in curriculum planning -- England; Educational change -- England